Base Composition of Deoxyribonucleic Acid Isolated from Mycobacteria - Wayne, Lawrence G. (1968)
Guanine plus cytosine values of deoxyribonucleic acid derived from 30 cultures representing 14 mycobacterial species or varieties are presented. These data provide impressive reasons for maintaining the separation between the genera Corynebacterium and Mycobacterium; no conclusions can be arrived at from these data with respect to the Nocardia-Mycobacterium relationship. A bimodal clustering, in terms of guanine plus cytosine composition, is apparent within the genus Mycobacterium. In general, all members of any single phenetic species appear to fit into one or another of these clusters. The phenetic separation of species is, in some cases, confirmed by separation in terms of guanine plus cytosine values. The bimodal separation of guanine plus cytosine values within the genus Mycobacterium does not correspond to a division of the species into slow and rapid growers; it thus provides no justification for splitting Mycobacterium into two genera, composed of slow and rapid growers. This is not to say that such a split would not be useful, only that these data do not contribute to such a decision. Any further attempts to correlate phenetic classification with properties of mycobacterial deoxyribonucleic acid will require more specific techniques, such as molecular hybridization.